An Analysis of Illocutionary Acts Performed by The Two Main Characters in "The Proposal" Movie" - Rinda Riztya; Sofia F Rahmani (ESENSI LINGUA, 2022)
The study is aimed at finding out the types and the dominant type of illocutionary act in The Proposal movie. This research is conducted by descriptive quantitative design, which makes a description of the situation or event/ occurrences. The data in this analysis is the transcript of The Proposal movie which was taken from the internet, and it focuses on the major characters’ utterances. The finding shows that there are 302 illocutionary utterances. Each illocutionary act classification includes assertives 161 (53.31%), directives 111 (36.75%), commissives 9 (2.98%), expressives 12 (3.97%), and declarations 9 (2.98%). The sub-classifications of illocutionary acts are found including: assertives; reporting, stating, suggesting, calling, complaining. directives s; requesting, ordering, asking, recommending. commissives; promising, offering, rejecting. expressives; praising, thanking, congratulating, blaming, apologizing. declarations; excommunicating and refusing.